Leishmanicidal activity of a daucane sesquiterpene isolated from Eryngium foetidum. (March 2014) - Rojas-Silva, Patricio; Graziose, Rocky; Vesely, Brian; Poulev, Alexander; Mbeunkui, Flaubert; Grace, Mary H.; Kyle, Dennis E.; Lila, Mary Ann; Raskin, Ilya
Abstract Context: Eryngium foetidum L. (Apiaceae) is a traditional herb that has been used for numerous medicinal applications, including as a treatment for parasitic infections, especially in the Neotropics from where it originates. Objective: This study evaluates the in vitro leishmanicidal and cytotoxicity activities of isolated compounds based on a bioassay-guided fractionation approach. Materials and methods: Defatted aerial parts of E. foetidum were subjected to extraction with methanol followed by partitioning with n-hexane, ethyl acetate and 50% methanol. Then, the first two fractions were subsequently fractionated by column chromatography and HPLC. Compound identity was confirmed by mass spectrometry and NMR spectroscopy. Leishmania tarentolae (promastigotes) and L. donovani (amastigotes) were used as testing parasites. L6 rat myoblasts were used for cytotoxicity. All extracts and fractions were tested at 20 μg/mL. Results: The initial methanol extract showed 20% growth inhibition of L. tarentolae. Then, the n-hexane and ethyl acetate fractions were also active showing approximately 40% growth inhibition. From these two fractions, the following compounds were isolated: lasidiol p-methoxybenzoate (1), a daucane sesquiterpene; and 4-hydroxy-1, 1, 5-trimethyl-2-formyl-cyclohexadien-(2, 5)-[α-acetoxymethyl-cis-crotonate] (2), a terpene aldehyde ester derivative. Compound 1 inhibited the growth of both L. tarentolae and L. donovani with IC50 values of 14.33 and 7.84 μM, respectively; and showed no cytotoxicity (IC50 > 50 μM). Compound 2 was inactive in the L. tarentolae assay (IC50 > 50 μM). Discussion and conclusion: This study presented the bioassay-guided fractionation with the leishmanicidal and cytotoxicity activities of two compounds isolated for the first time from an Eryngium species.